SEDIMENT DISTRIBUTION PATTERNS ANALYSIS AT SHORELINE CHANGED AREAAROUND CAROLINA BEACH PADANG CITY WEST SUMATERA PROVINCE - Prastya Bayu Afrian; Rifardi Rifardi; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe study was conducted in Desember 2017 to March 2018 in the Carolina Beach Padang City West Sumatera Province. The purpose of the study was to determine the characteristic of sediment in the area based on sediment grain size distribution, fraction sediment type, sediment statistic parameters and sediment compotition. The metdhod used was survey with purposive sampling method, where the location of study was divided into 10 sampling points across the shoreline changed area. The result showed that the study area was dominated by muddy sand sediment with sediment compotition of lithogenous. Based on their sediment characteristic location of study was divided into 3 area,  (1) abration area, (2) accretion area and (3) estuary area. Founded that there were sediment fraction difference between the accretion area and abration area. Key words: Characteristic of Sediment, Shoreline Change, Carolina Beach